Pengetahuan Konseptual Biologi Siswa SMA di Aceh - Silvi Puspa Widya Lubis; Paidi; Samsuar; Putri Dini Meutia; Syarifah Rahmiza Muzana; Ferlya Elyza; I Gusti Putu Suryadarma (Jurnal Serambi Ilmu, 2024)
This research was descriptive research using the survey method. This research was conducted at the Public Senior High School, Aceh Besar, Aceh in 2019. The research subjects were 135 students of class X SMAN in Aceh Besar. The sampling technique was the total sampling technique. Data collection was done through test techniques. The test technique was carried out to measure the achievement of conceptual abilities. The test instrument used was multiple choice taken from ecosystem material. The data analysis used was inferential analysis to determine the difference in the achievement of students’ conceptual knowledge in schools with the accommodated variables, namely based on gender. The results obtained indicate that the results of the study obtained a value of p = 0.000 (p <0.05), so there is a significant difference between the gender of female and male students. The average value of the achievement of conceptual knowledge of students of class X IPA SMA Negeri in Aceh Besar where the female students were 8,96 and male students were 4.36. It can be concluded that the conceptual knowledge of female students is higher than male students.